ITRACONAZOLE-LOADED NANOEMBEDDED MICROPARTICLES FOR INHALATION THERAPY IN LUNG INFECTIONS: DESIGN AND OPTIMIZATION - INDIRA MUZIB YALLMALLI; SREEVIDYA PUVVALA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: To develop and optimize itraconazole (ICZ) nanoembedded microparticles (NMPs) for pulmonary delivery to enhance the treatment of aggressive pulmonary fungal infections, such as aspergillosis, in immunocompromised patients with chronic respiratory conditions by improving ICZ solubility, dissolution, and lung-specific drug delivery. Methods: Itraconazole nanocrystals (INCs) were formulated using ultrasonic processing with Poloxamer-188 or Brij 58 as stabilizers to enhance solubility. Quality by Design (QbD) principles were applied to evaluate the effects of formulation and process variables on ICZ solubility and dissolution. Optimized INCs were lyophilized into NMPs using α-Lactose Monohydrate USP as a matrix, sifted to a particle size of <5 µm, and subjected to micromeritic and dissolution studies. The pharmacokinetic performance of NMPs was compared to commercially available oral ICZ formulations by assessing plasma drug concentrations. Results: Optimized INCs, sonicated with Poloxamer-188 at 50% amplitude for 15 minutes, achieved a particle size of 174.4 nm, solubility of 0.31 mg/mL, and a dissolution time of 22.97 minutes to reach 90% of the dose. NMPs exhibited suitable properties for inhalation, disintegrating in the secondary bronchi to release INCs that rapidly penetrated alveolar fluids. Compared to oral formulations, NMPs showed a faster tmax, higher Cmax, and increased plasma ICZ bioavailability at equivalent doses, with significantly higher drug concentrations in the lungs and sustained effective levels. Conclusion: ICZ-loaded NMPs for pulmonary delivery offer a promising approach for treating pulmonary fungal infections, providing enhanced solubility, rapid dissolution, and superior lung-targeted drug delivery compared to oral formulations, potentially improving therapeutic outcomes in vulnerable populations.